Spurious harmonic suppression in compact coupled-line bandpass filter with asymmetric perturbations. Issue 4 (2nd April 2020) - Das, Tarun Kumar; Chatterjee, Sayan
ABSTRACT: Present article exhibits the design of a third-order compact parallel-coupled line bandpass filter at 5.25 GHz having asymmetric perturbations to suppress the second harmonic. Initially, the effects of compactness on filter characteristics have been studied by synthesising the distributed filter network into its equivalent circuit model. The design has been initiated by computing the unit cell model, which leads to the first-order and third-order design instances with an improvement in compactness over the traditional parallel-coupled line filter. In contrary, compactness in the filter characteristics degrades the second harmonic level subject to enhanced imbalances among the odd- and even-mode velocities at the coupled lines. Subsequently, the improvement in the harmonic suppression of 53 dB and 58 dB has been achieved by incorporating different non-uniform perturbations to the outer and coupled edges of the compact filters. Accordingly, compactness of 58% and 71% have been obtained subject to the folded and in-line designs over the conventional layout.